Physical therapy vs. glucocorticoid injection in patients with meniscal tears and knee osteoarthritis: a multi-center, randomized, controlled trial - Mingzhu Lee; Chao Jing; Kainan Lee (BMC Medicine)
Abstract Background Physical therapy is commonly recommended for treating meniscus tears and knee osteoarthritis (KOA). However, data from randomized trials that compare the effectiveness of this treatment with that of glucocorticoid injections are lacking. Methods This randomized, single-blind, multicenter trial included 273 patients with KOA who were divided into either the physical therapy group (n = 133) or the glucocorticoid injection group (n = 140). The physical therapy included kinesiology tape, exercise protocols, and exercise training programs to increase core stability and periprosthetic muscle strength. The primary endpoint was the overall Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) score at 1 year. Additionally, proprioception and safety were assessed. All analyses were performed with the use of the intention-to-treat approach. The data are reported as percentages (%) (n), and the threshold for statistical significance was p < 0.05. Results There was no significant difference in the baseline characteristics between the two groups (p > 0.05). The average (± SD) WOMAC score at 1-year was 76.85 ± 2.50 in the physiotherapy group. And 99.55 ± 2.09 in the glucocorticoid injection group (mean difference = − 22.70; 95% confidence interval [95% CI] − 23.43 to − 21.96; p < 0.001). Compared with the glucocorticoid injection group, the physical therapy group exhibited superior performance in terms of proprioception, especially in the eyes-closed in situ stepping test (14.27 ± 0.75 versus 5.98 ± 0.74; mean difference = 8.29; 95% CI 8.09–8.50; p < 0.001). The incidence of serious adverse events at the 1-year follow-up was comparable between the two groups. Most of these events were determined to be complications arising from physical therapy and glucocorticoid injection. Conclusions The results revealed that pain, quality of life, and balance were greater in the physiotherapy group than in the glucocorticoid injection group within the 1-year study period. However, the long-term effects beyond this timeframe remain unknown, and future studies with extended follow-up times are needed to confirm the sustainability of these benefits. Trial registration The protocol was approved by the local ethics committee of the ethical commission of the Hebei Sports Science Research Institute (SEC20200213019) and Ethics Committee of Sichuan Taikang Hospital (SCTK-IRB-032). The study was registered at the Chinese Clinical Trial Registry (ChiCTR2000032508).